Unlicensed EFL Teachers Co-constructing Knowledge and Transforming Curriculum Through Collaborative-Reflective Inquiry - Aguirre Garzón, Edgar Augusto (Profile: Issues in Teachers’ Professional Development, 2018)
This paper describes a case study research project carried out in a public school in Bogotá, Colombia, with four unlicensed teachers of English as a foreign language. Although the institutional guidelines in the school suggest that teachers should collectively propose changes to shape pedagogical realities, there is evidence of little communication among them. This study emphasizes collaborative, reflective inquiry as a means to educative transformation. Findings suggest that collaborative inquiry prompts the language teachers to conjointly design teaching strategies and materials that articulate with students’ contexts. Furthermore, along the way, the teachers were empowered to propose curricular changes to adjust contents and goals of the area with the students’ contextual reality.